Tes Kecepatan dan Performa dalam Bola Tangan Unimed Speed Test Performance In Unimed Handball - Niada Zai; Evalince Agnes Amo; Palmarum Glenovian Hutahean; Ayu Tamara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and compare the speed performance of handball athletes and non-athletes at Universitas Negeri Medan (UNIMED). Speed is a fundamental component influencing both offensive and defensive performance in handball. This research used a quantitative comparative approach. The subjects consisted of 10 participants, including 6 athletes and 4 non-athletes from the UNIMED Handball Club. The instrument used was a 20-meter sprint test. Data were analyzed using descriptive statistics and an independent sample t-test (α = 0.05). The results showed that the average sprint time was 3.31 seconds, with the fastest time of 2.98 seconds and the slowest time of 3.70 seconds. Athletes demonstrated a faster average time (3.09 seconds) compared to non-athletes (3.63 seconds). The t-test result showed a significant difference between groups, t(8) = -6.12, p < 0.05. It can be concluded that there is a statistically significant difference in speed between athletes and non-athletes, indicating the importance of structured training in improving overall athletic ability